ANALISIS PARTISIPASI POLITIK PADA PEMILUKADA PROVINSI RIAU PUTARAN PERTAMA TAHUN 2013 DI KECAMATAN AGARAN TAPAH DARUSSALAM KABUPATEN ROKAN - Afriana Dewita Syafitri; M.Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study wanted to see the level of participation on Election tenatgn Riau first round in 2013 in District Pagaran Tapah Darussalam Rokan Hulu. The problem is the background of this study is why many people Pagaran Tapah Darussalam District of Rokan Hulu no participation in Riau Province in 2013 Election? This study is a qualitative research, the data collection techniques in this study is a descriptive analysis. This study uses interviews with key informants as information objects that aim to achieve the goal in order to get information in this study, and supported also by questionnaire. Data used in this study is primary data and secondary data obtained through interviews with key informants. Based on the results of such research are dipaparpakan before, it can be deduced that the number of people in the District Pagaran Tapah Darussalam who did not participate in Riau Province Election Year 2013 First Round in the District Pagaran Tapah Darussalam was due to a lack of political socialization of the candidates who competed in the Provincial Election Videos First Round in 2013 and the lack of public trust in government, so people assume that anyone elected leaders will not be able to bring a good change to the community.Keyword : Partisipasi Politik, Pemilukada, Pemilu